METHODOLOGICAL APPROACHES FOR MANAGING INNOVATION PROCESSES IN AGRICULTURAL ENTERPRISES - Khanas , В. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article explores methodological approaches to managing innovation processes within agricultural enterprises. It identifies the key drivers that encourage these enterprises to develop and implement innovations and emphasizes the role of methodological adherence in identifying the most promising areas of innovation as well as in evaluating their contribution to achieving strategic objectives. The selection of management methods is shown to be directly dependent on the specific nature of agricultural activities, where technological processes in the natural environment and biological systems may serve as primary objects of innovation. Innovation process management in agricultural enterprises is considered through the lens of a systematic approach, which integrates the analysis of all influencing factors - from idea generation to implementation and performance monitoring. The study outlines the principal factors necessitating the adoption of modern management methods in agricultural innovation and models the sequence of stages in innovation management within a systematic framework. A set of methods for managing innovation processes is systematized and characterized, including questionnaires, assessments, SWOT analysis, matrix techniques, ranking, planning, monitoring, observation, control, and mathematical modeling. In particular, SWOT analysis provides a comprehensive overview of both the potential and the challenges associated with innovation in agricultural enterprises, serving as the foundation for strategy development aimed at leveraging strengths and opportunities while minimizing weaknesses and mitigating threats. Monitoring and evaluation methods are highlighted as essential for tracking progress and assessing outcomes, drawing on both internal and external information sources. The findings suggest that the assessment of innovation effectiveness enables the development of balanced management mechanisms designed to stimulate production and business processes, enhance profitability, and ensure the continuity and resilience of agricultural enterprises.